Association of factor expression levels with annual bleeding rate in people with haemophilia B. Issue 1 (4th November 2022) - Burke, Tom; Shaikh, Anum; Ali, Talaha M.; Li, Nanxin; Konkle, Barbara A.; Noone, Declan; O'Mahony, Brian; Pipe, Steven; O'Hara, Jamie
Abstract: Introduction: Gene therapy clinical trials measure steady‐state clotting factor expression levels (FELs) to evaluate the modulation of the bleeding phenotype, aiming to offer consistent protection against breakthrough bleeding events. The link between FELs and bleeding risk in people with haemophilia B (PwHB) is not well understood. Aim: We evaluated the association between FEL and ABR in PwHB. Methods: This cross‐sectional study extended the CHESS burden of illness studies in Europe and the United States. Recruitment of additional adult males with haemophilia B supplemented the existing CHESS sample size of PwHB and FELs. PwHB receiving prophylaxis were excluded, as fluctuating FELs may have confounded the analysis. Demographic and clinical characteristics were reported descriptively. Any recorded baseline FEL was reported by the haemophilia‐treating physicians according to the medical records. Generalised linear models with log link explored the association between changes in FEL and ABR. Results: The study included 407 PwHB and no inhibitors receiving on‐demand treatment. Mean age was 36.7 years; 56% from the EU, 44% from the United States. Mean baseline FEL was 9.95 IU/dl (SD, 10.47); mean ABR was 2.4 bleeds/year (SD, 2.64). After adjusting for covariates, the model showed that for every 1% increase in FEL the average ABR decreased by .08 ( p < .001). Predicted number of bleeding events according to FEL showed a significant non‐linear relationship between FEL and ABR ( p < .05). Conclusion: This analysis showed a significant relationship between FEL and ABR, where increases in FEL were associated with decreases in ABR among men with HB in Europe and the US.